Equilibrium and thermodynamic studies of stearic acid adsorption on Celtek clay - AHMET SARI; MUSTAFA SOYLAK (Journal of the Serbian Chemical Society, 2007)
This paper presents the equilibrium and thermodynamic parameters of the adsorption of stearic acid on Celtek clay as a function of temperature. It was found that the adsorption of stearic acid on Celtek clay decreased with increasing temperature from 293 to 313 K. The equilibrium modelled data fitted well with the linear forms of both the Langmuir and the Freundlich models (R2 = 0.99 in both cases). The RL and 1/n values determined from the isotherm models proved that Celtek clay is a suitable adsorbent for stearic acid. The Dubinin–Radushkevich (D–R) isotherm was applied to describe the nature of the adsorption of stearic acid on Celtek clay and it was found that the adsorption occurred physically. Thermodynamic parameters of adsorption, such as Gibbs free energy change (ΔG0), enthalpy change (ΔH0) and enthropy change (ΔS0) were also calculated. These parameters showed that the adsorption of stearic acid on Celtek clay was feasible, spontaneous, and exothermic in nature. On the basis of the results, it can be concluded that Celtek clay has considerable potential for the removal of stearic acid from the main sources, such as raw and edible soybean, sunflower and olive oils.